The COVID-19 Crisis Response : Supporting Tertiary Education for Continuity, Adaptation, and Innovation - World Bank (World Bank, Washington, DC, 2020)
Tertiary education is vital for producing the caliber and diversity of graduates needed both for the economy that exists today and for economy to which a nation aspires. It fuels competitiveness and growth by preparing professionals, like managers and engineers, medical personal and teachers. Universities are also centers of research and innovation and – working with small and medium size enterprises – support regional development. Tertiary education is both the aspiration of more and more young people around the globe and a fundamental requirement for employment in the industries that drive the global knowledge economy. As such, tertiary education provides unique opportunities for individual development and equality of opportunity as well as promoting shared prosperity. A failure to sustain effective tertiary systems can lead to perilous social upheavals, as youth fall outside the education system, unable to engage in active learning and uncertain about the future of their education and prospects. Societies are, then, confronted with a massive challenge of youth disengagement and deprived of the graduate professionals needed to keep countries on track for social cohesion and growth.